Cystic fibrosis in black African children in South Africa: a case control study - Kwarteng, Owusu Sandra (Department of Paediatrics and Child Health, 2020)
Background Cystic fibrosis (CF) is described more commonly in Caucasian populations in whom p.Phe508del is the most common mutation. There is a paucity of data of CF in black African children. The aim of this study was to describe and compare the presentation and outcomes of black African children with CF to those with p.Phe508del genotype. Methods A retrospective case-controlled study was conducted from January 2000 – March 2018 of children with CF attending two CF centres in South Africa. Presentation, genotype, nutrition and pulmonary function outcomes of black African children were compared to matched controls with the p.Phe508del mutation. Results Thirty-four black African children (cases) with median age of diagnosis (5.5 months, IQR 2.0- 15.0) were matched to 34 controls. Among cases, 3120+1G->A CFTR mutation was most commonly identified; homozygous n=22 (64.7%) and heterozygous=7(20.5%). Compared to controls, cases at diagnosis were more malnourished and fewer presented with neonatal bowel obstruction [cases n=2 (5.9%) vs. controls n=10 (29.4%); p = 0.03]. Nutrition and pulmonary function (FEV1 in children ≥ 6 years) outcomes and changes over time from ages 3-16 years were similar in both groups; median FEV1 z-score at age 6,10 and 14 years was -0.9 (±1.5), -1.8 (±2.0) and -1.8 (±1.9) respectively for all patients. Deaths were recorded in three cases (8.8%) and one control (2.9%) (p = 0.6). Conclusion Black African children with CF were more malnourished at diagnosis, and fewer presented with neonatal bowel obstruction. Cases and controls had comparable nutritional, pulmonary function and early mortality outcomes.